The protective effects of melatonin against water avoidance stress-induced mast cell degranulation in dermis - ERCAN, FERİHA; ŞENER, GÖKSEL (ELSEVIER GMBH, 2005)
Nontraumatic psychological water avoidance stress has been shown to induce mucosal. degeneration, inflammatory cell infiltration and mast cell degranulation in stomach, ileum, colon and urinary bladder. Many skin disorders, such as atopic dermatitis and psoriasis, worsen during stress and seem to be related with infiltration and activation of mast cells releasing vasoactive and proinflammatory mediators. Melatonin is a free radical scavenger and has cytoprotective effects in inflammatory conditions. The aim of the present study was to investigate the effects of melatonin on water avoidance stress (WAS)-induced degranulation of mast cells in the dermis. Wistar rats were exposed to acute WAS (aWAS group) or chronic WAS (cWAS group). Before exposing to acute WAS, one group of animals was treated with 10mg/kg metatonin (aWAS+mel. group). In the cWAS+mel group, treatment with melatonin lasted for 5 days. Dermal mast cells were stained with toluidine blue and investigated using light microscopy. Numbers of mast cells were increased in both aWAS and cWAS groups, but numbers of degranulated mast cells were increased significantly only in the cWAS group when compared to the control group. Numbers of mature granulated and degranulated mast cells were decreased in the cWAS+mel. group when compared to the cWAS group. In conclusion, chronic metatonin treatment reduced WAS-induced infiltration and activation of mast cells in dermis and may provide a useful therapeutic option in stress-induced skin disorders. (c) 2004 Elsevier GmbH. All rights reserved.
Keywords: water avoidance stress; mast cells; degranulation; melatonin; CORTICOTROPIN-RELEASING HORMONE; PITUITARY-ADRENAL AXIS; VASCULAR-PERMEABILITY; SUBSTANCE-P; SKIN; RAT; NEUROTENSIN; SECRETION; INFLAMMATION; NEURONS